An Evaluation Model For A Human Rights-Based Cultural Heritage System - Eryazicioglu, Erdem; Cengiz, Huseyin (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2018)
With the introduction of the concept of 'cultural heritage for society,' cultural heritage addressed in the context of human rights, and human rights have been involved in the relevant theory and practice of cultural heritage. The present study aims to identify the characteristics that a cultural heritage system on a universal, national or local scale should have in order to be human rights-based and to form an evaluation model. The study suggests that a rights-based understanding of cultural heritage will be more successful in practice. It is argued as a basic view that the main objective is to protect the rights, and a society and horizontal organization-based system, where power and responsibility are shared with all stakeholders, would allow for the effective protection of cultural heritage and for the achievement of human rights. In this context, three inter-related issues are discussed in the article. The study beg ins with the examination of human rights and the stage in which the idea of human rights reaches today is revealed. Secondly, the changes in the understanding of cultural heritage and the reflections of different aspects of this change of heritage are explained. Following the examination of the place of cultural heritage theory and practice in human rights, finally the characteristics of the cultural heritage system based on human rights are presented as a synthesis.
Keywords: Rights-based cultural heritage system; human rights; conservation; cultural heritage; AUTHENTICITY; MANAGEMENT; DIVERSITY; Architecture